Atlas of Diffuse Lung Diseases : A Multidisciplinary Approach - Dalpiaz, Giorgia; Cancellieri, Alessandra (Springer International Publishing : Imprint: Springer, 2017)
This atlas is designed as an easy-to-use reference guide that identifies and illustrates the key patterns of diffuse lung diseases observed on high-resolution computed tomography (HRCT) and then documents in more detail the characteristics and appearances of the individual diseases, grouped on the basis of their prevalent pattern. A further feature of the book is its interdisciplinary nature: contributions from experts in various specialties are tightly interwoven throughout and many pathologic correlations are included. Less experienced readers will find that this atlas, with its wealth of figures and helpful color coding, steers them towards correct interpretation when confronted by the multiplicity and complexity of these diseases; those who are already experts, on the other hand, will benefit from the detailed coverage of individual diseases, which will deepen their understanding. At the end of the book, a graphically appealing and practice-oriented illustrated glossary with tips and tricks offers a further highly effective educational tool. Given the clinical spectrum of diseases covered, this atlas will prove invaluable for a wide range of healthcare workers, especially radiologists, pulmonologists, and pathologists.
Keywords: Medicine.; Radiology.; Respiratory organs -- Diseases.; Pathology.; elektronické knihy; electronic books